THE MEANING OF “MEANING” IN AL-ATTAS’ “THE ARRIVAL IN THE SOUL OF THE MEANING OF A THING” - Baharuddin AbdRahman (Sekolah Tinggi Agama Islam Indonesia Jakarta, 2019)
In Islam, knowledge is said to be true and real knowledge if it is useful (yantafi‘u) that is measured when someone knows (‘arafa) himself with whom someone knows God and his destiny. This research is an exposition of the nature of knowledge in the perspective of al-Attas. Using the library research method, this research found that ma'na (meaning), as stated in the definition of knoeledge (حصول معنى الش يئ فى النفس ) means: (1) to put everything in its rightful portion and position, (2) everything is a symbol that refers to and point to something other than itself, ie, God, and (3) the condition of things constantly in a state of “recreation” and “annihilation” i.e., from being to nothing, then becoming again and so on.